PRELIMINARY STUDY ON NEWLY DETECTED YAYLIYAKA MARSHES IN THE LAKE VAN BASIN, TURKEY - Ö. Adizel; A. Durmuş; İ. Kiziroglu (Journal of Animal and Plant Sciences, 2010)
Yaylıyaka Marshes (38º, 49´ N; 043º, 23´ E) is located between Yaylıyaka and Kumluca Villages in the southeast shore of Lake Van. The area did not grab attention of researches because of its distance from the high way. Its length is 8.5 km and has 10-12 km2 surface area approximately. Review of the ornithological and ecological studies carried out in previous years revealed that no information related to this area exists. As many as 137 bird species belonging to 39 families (2 of them are subspecies) were identified in the study area. Of these, 67 (48.9%) are migrant species (summer migrant), 50 (36.5%) are resident, 19 (13.87%) are winter visitors and 1 (0.73%) is transit migratory These species belong to different IUCN Red List Categories including; 2 (1.46%) species are critically endangered, 4 (2.9%) are endangered, 17 (12.4%) are vulnerable, 16 (11.68%) are near threatened, 88 (64.23%) are least concern, 3 (2.19%) are data deficient and 7 (5.1%) are not evaluated. According to Red Data Book List of Turkey, birds can be categorized as; A.1.2. 12 (8.76%), A.2. 22 (16.05%), A.3. 38 (27.74%), A.3.1. 21 (15.33%), A.4. 14 (10.22%), A.5. 20 (14.6%), B.3. 3 (2.2%), B.3.1. 1 (0.73%), B.4. 3 (2.2%) and B.5. 3 (2.2%). The most convenient protection method in such big basins is to protect the sections where living things live extensively. Therefore, the detection of Yaylıyaka Marshes will provide a significant contribution to basin protection plan.
Keywords: Lake Van; Wetlands; Yaylıyaka Marshes; Birds; Marshes